Eidinemacheilus proudlovei, a new subterranean loach from Iraqi Kurdistan (Teleostei; Nemacheilidae) - Freyhof, Jörg; Abdullah, Younis Sabir; Ararat, Korsh; Ibrahim, Hamad; Geiger, Matthias F. (Zootaxa, 2016)
Eidinemacheilus proudlovei, new species, is described from subterranean waters in the Little Zab River drainage in Iraqi Kurdistan. After the discovery of E. smithi in 1976, E. proudlovei is the second troglomorphic nemacheilid loach found in the Middle East and the second species placed in Eidinemacheilus. Eidinemacheilus proudlovei is distinguished from E. smithi by having 8+8 or 8+7 branched caudal-fin rays, no adipose keel on the caudal peduncle, enlarged jaws and a fully developed head canal system. It furthers differs substantially in its DNA barcode (>8% K2P distance) from all other nemacheilid loaches in the Middle East, Europe and Western India.